Diversity and drivers of marine heatwaves in the Beibu Gulf of the South China Sea - Bo Zhang; Qiang Wang; Lili Zeng; Kunshan Li; Yi Xie; Rui Shi (Climate Dynamics, 2026)

Spring Arctic sea ice decline exacerbates summer extreme precipitation in central Asia and drought in northeast China - Lingzhi Zhang; Weiliang Qiu; Qianrong Ma; Li Chen; Rui Hu; Zhonghua Qian; Pengcheng Yan; Guolin Feng (Climate Dynamics, 2026)

Monthly variations of the spring greenness response across boreal Eurasia to the preceding wintertime northern annular mode during 1982–2022 - Jing Li; Weiming Zeng; Ruichen Lin; Zhiqing Xu; Xilin Xie; Feng Su; Rui Zhao; Anmin Duan (Climate Dynamics, 2025)

Quantile delta-mapped spatial disaggregation analysis for summertime compound extremes over China - Rui Zhao; Xiong Zhou; Yongping Li; Jing Liu; Guohe Huang; Pangpang Gao (Climate Dynamics, 2024)

Influence of the Southern Ocean Dipole on the inter-model diversity of temporal trend of the austral summer Southern Annular Mode in CMIP6 models - Rui Wang; Fei Zheng; Xiaofeng Li (Climate Dynamics, 2024)

The influence of complex terrain on cloud and precipitation on the foot and slope of the southeastern Tibetan Plateau - Junjun Li; Chunsong Lu; Jinghua Chen; Xu Zhou; Kun Yang; Jian Li; Xiaoqing Wu; Xiaoqi Xu; Shiying Wu; Rui Hu; Xin He; Zhuangzhuang Zhou; et al. (Climate Dynamics, 2024)

Evaluation of the performance of the latest WRF model (V4.5) in simulating surface elements and its sensitivity to the diurnal SST cycle in the South China Sea - Rui Shi; Ju Chen; Yunkai He; Wei Song; Daning Li; Yeqiang Shu; Dongxiao Wang (Climate Dynamics, 2024)

The reduced Siberian spring snow cover modulation on southward northernmost margin of East Asia summer monsoon - Shiying Wu; Jie Zhang; Junjun Li; Zhiheng Chen; Yun Hang; Miaomiao Niu; Yuxin Kuang; Rui Hu (Climate Dynamics, 2023)

Predictability of spatial distribution of pre-summer extreme precipitation days over southern China revealed by the physical-based empirical model - Juan Li; Changshan Zheng; Ying Yang; Rui Lu; Zhiwei Zhu (Climate Dynamics, 2023)

The two leading modes of winter clear-sky days over China and their formation mechanisms - Huiping Yan; Xiao Pan; Zhiwei Zhu; Rui Lu; Linfei Li; Hui Tan (Climate Dynamics, 2021)

Enhancement of the summer extreme precipitation over North China by interactions between moisture convergence and topographic settings - Yang Zhao; Deliang Chen; Jiao Li; Dandan Chen; Yi Chang; Juan Li; Rui Qin (Climate Dynamics, 2020)
This study investigates the roles of atmospheric moisture transport under the influence of topography for summer extreme precipitation over North China (NC) during 1979–2016. Based on rain gauge precipitation data and a reanalysis, 38 extreme precipitation days in NC during the 38 years were selected and associated moisture fluxes estimated. The results show that there is a dominant moisture influx of 311.8 kg m −1 s −1 into NC along its southern boundary from tropical oceans, and a secondary influx of 107.9 kg m −1 s −1 across its western boundary carried by mid-latitude westerlies. The outflux across the eastern boundary is 206.9 kg m −1 s −1 and across the northern boundary is 76.0 kg m −1 s −1 , giving a net moisture gain over NC of 136.8 kg m −1 s −1 . During extreme precipitation days, the moisture flux convergence (MFC) was much larger, exceeding 4 × 10 −5 kg m −1 s −1 . The MFC maximum core, the pronounced moisture transport, and the striking extreme precipitation zone over NC are all anchored to the east of the steep slopes of the surrounding topography. Moreover, a remarkably high humidity and strong upward motion also occur near steep slopes, indicating the critical role of the adjacent topography on the extreme precipitations. Simulations with and without the topography in NC using the Weather and Research Forecasting model for six selected out of the 38 extreme precipitation days demonstrate that the surrounding topography reinforces the MFC over NC by 16% relative to the case without terrain, primarily through enhanced wind convergence and higher moisture content, as well as stronger vertical motion induced by diabatic heating. The interactions between moisture convergence and topographic settings strengthen the extreme precipitation over NC.

The influence of wave trains in mid-high latitudes on persistent heavy rain during the first rainy season over South China - Rui Miao; Min Wen; Renhe Zhang; Lun Li (Climate Dynamics, 2019)

Precipitation characteristics over the steep slope of the Himalayas in rainy season observed by TRMM PR and VIRS - Yunfei Fu; Xiao Pan; Tao Xian; Guosheng Liu; Lei Zhong; Qi Liu; Rui Li; Yu Wang; Ming Ma (Climate Dynamics, 2018)

Boreal winter Arctic Oscillation as an indicator of summer SST anomalies over the western tropical Indian Ocean - Dao-Yi Gong; Dong Guo; Yongqi Gao; Jing Yang; Rui Mao; Jingxuan Qu; Miaoni Gao; Sang Li; Seong-Joong Kim (Climate Dynamics, 2017)